Primary Non-Hodgkin’s Lymphoma of Bone Arising from Hip - Lamichhane, A; Mahara, D (Journal of Nepal Health Research Council, 2013)
Non-Hodgkin’s lymphoma can present as either a nodal form with local or regional lymphadenopathy or less commonly, as an extranodal form outside the lymphatic system. Primary lymphoma of bone (PLB) is uncommon malignancies. Here we present a case of primary non-Hodgkin’s lymphoma of bone arising from hip with clinical and radiological diagnostic difficulty. Keywords: lymphadnenopathy; malignancies; Non-Hodgkin’s lymphoma; primary bone lymphoma.